Effect of recreational‐fisheries management on fish biodiversity in gravel pit lakes, with contrasts to unmanaged lakes - Sven Matern; Matthias Emmrich; Thomas Klefoth; Christian Wolter; Robert Nikolaus; Nicola Wegener; Robert Arlinghaus (Journal of Fish Biology, 2019)
Gravel pit lakes are novel ecosystems that can be colonized by fish through natural or anthropogenic pathways. In central Europe, many of them are managed by recreational anglers and thus experience regular fish stocking. However, also unmanaged gravel pits may be affected by stocking, either through illegal fish introductions or, occasionally, by immigration from connected water bodies. We sampled 23 small (